Relevance of Pharmacogenomics and Multidisciplinary Management in a Young-Elderly Patient With KRAS Mutant Colorectal Cancer Treated With First-Line Aflibercept-Containing Chemotherapy - Bruera, Gemma; D'Andrilli, Antonio; Simmaco, Maurizio; Guadagni, Stefano; Rendina, Erino Angelo; Ricevuto, Enrico (Frontiers in Oncology, 2020)
Introduction: Intensive oncological treatment integrated with resection of metastases raised clinical outcome of metastatic colorectal cancer (MCRC). In clinical practice, complex evaluation of clinical (age, performance status, comorbidities) and biological (tumoral genotype, pharmacogenomic) parameters addresses tailored, personalized multidisciplinary treatment strategies. MCRC patients unsuitable for first line intensive medical treatments are prevalent and showed worse clinical outcome. After progression to oxaliplatin-based chemotherapy, aflibercept/FOLFIRI significantly improved clinical outcome, even if no survival benefit was reported in adjuvant fast relapsers by aflibercept addition. The case reported a young-elderly (yE), KRAS mutant colorectal cancer patient rapidly progressing to adjuvant chemotherapy, unfit due to comorbidities, with multiple pharmacogenomic alterations, who gained long-term survival in clinical practice by multidisciplinary treatment strategy consisting of first line and re-introduction of aflibercept-containing chemotherapy and two-stage lung metastasectomies. Case presentation: A 71 years-old yE patient, unfit for intensive oncological treatments due to Cumulative Illness Rating Scale (CIRS) stage secondary, affected by KRAS c.35 G>T mutant colorectal cancer, rapidly progressing with lung metastases after adjuvant XelOx chemotherapy, reached long-term survival 66 months with no evidence of disease, after first line and re-introduction of tailored, modulated aflibercept (4 mg/Kg) d1,15 - irinotecan (120 mg/m2) d1,15 – 5-fluorouracil (750mg/m2/d) dd1-4, 15-18, and secondary radical bilateral two-stage lung metastasectomies. Safety profile was characterized by Limiting Toxicity Syndrome at multiple sites (LTS-ms), requiring 5-fluorouracil discontinuation and aflibercept reduction (2 mg/kg), due to G2 hand-foot syndrome (HFS) for >2 weeks, and G3 hypertension. Pharmacogenomic analyses revealed multiple alterations of fluoropirimidine and irinotecan metabolism: severe deficiency of fluorouracil degradation rate (FUDR), single nucleotide polimorphisms (SNP) of UGT1A1*28 variable number of tandem repeats (VNTR) 7R/7R homozygote, ABCB1 c.C3435T, c.C1236T, MTHFR c.C667T homozygote, DPYD c.A166G, TSER 28bp VNTR 2R/3R heterozygote. Conclusions: In clinical practice, a complex management evaluating clinical parameters and RAS/BRAF genotype characterizing individual MCRC patient, particularly elderly and/or unfit due to comorbidities, is required to properly address tailored, multidisciplinary medical and surgical treatment strategies, integrated with careful monitoring of superimposing toxicity syndromes, also related to pharmacogenomic alterations, to gain optimal activity and long-term efficacy.